Penerapan Kombinasi Metode ROC dan TOPSIS Pemilihan Karyawan Terbaik Untuk Rekomendasi Promosi Jabatan - Lince Tomoria Sianturi; Mesran Mesran (Journal of Computer System and Informatics (JoSYC), 2022)
Position promotion is a transfer or promotion of an employee in a structure within the organizational structure who has the ability to know skills and a responsible attitude in accordance with qualifications based on standards that exist in a company itself with specific functions. In the process of selecting the best employees, for recommendation for promotion, a measurable decision support system is needed. As in the POLDASU HR BUREAU, which does not yet have a decision support system, which so far has recommended promotions at the North Sumatra Regional Police, there are still obstacles in the criteria for evaluating promotions, so does not rule out the possibility that decision making is done subjectively by only looking at certain aspects and requires a long time in making decisions. In general, the recommendation for promotion is given by each work unit, good assessments from superiors and employee performance in carrying out their duties. For this reason, it is necessary to assess data processing employees who can help companies make decisions related to promotion recommendations. There needs to be supporting criteria for using a decision support system. In this study applied a combination of ROC and TOPSIS methods. The weighting of each criterion is carried out by applying the ROC method, then followed by a ranking process that will select the best alternative from a number of alternatives using the TOPSIS method. The TOPSIS method is a method that uses the principle that the chosen alternative must have the closest distance from the positive ideal solution and the farthest from the negative ideal solution. The results of the Research Recommendations for Promotion of Positions that are appropriate for promotion are alternative A1 with a preference value of 1,497 on behalf of "Hendrik".